2015
DOI: 10.1016/j.foreco.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Stand-level drivers of tree-species diversification in Mediterranean pine forests after abandonment of traditional practices

Abstract: a b s t r a c tThe progressive abandonment of traditional forest management over the last few decades has led to significant densification processes in most Mediterranean pine stands. In parallel, some of these stands have also shown tree-species diversification processes, the occurrence of which is considered essential for future adaptability and resilience to change. Here we aim to gain further understanding of the main factors driving these diversification processes via a case-study approach using the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
(76 reference statements)
1
20
0
Order By: Relevance
“…Based on the results, by 2015 there was a high increase in the number of recruits compared with 2005 (up to 5.9 times). A comparison of these results with those of Martín-Alcón et al (2015) shows an opposite trend because a decreasing number of recruits is reported in that paper. Such a trend is observed in other studies (Urbieta et al 2011;Carnier et al 2014).…”
Section: Diameter Growth With Respect To Environmental Conditionsmentioning
confidence: 58%
See 1 more Smart Citation
“…Based on the results, by 2015 there was a high increase in the number of recruits compared with 2005 (up to 5.9 times). A comparison of these results with those of Martín-Alcón et al (2015) shows an opposite trend because a decreasing number of recruits is reported in that paper. Such a trend is observed in other studies (Urbieta et al 2011;Carnier et al 2014).…”
Section: Diameter Growth With Respect To Environmental Conditionsmentioning
confidence: 58%
“…Such a trend is observed in other studies (Urbieta et al 2011;Carnier et al 2014). Martín-Alcón et al (2015) explain a decreasing number of recruits by the worse availability of light in forest stands. In other works a negative influence of the competition of herbaceous vegetation is mentioned (Lucas-Borja et al 2011;Prévosto et al 2012).…”
Section: Diameter Growth With Respect To Environmental Conditionsmentioning
confidence: 97%
“…Related to this topic, more information is available from the area of southern and northern Europe (Angelstam, Kuuluvainen 2004;Montes et al 2005;Poyatos et al 2013;Martín-Alcón et al 2015), but in conditions of central Europe researchers paid attention mainly to stands being composed of shade-tolerant species such as spruce, beech and fir.…”
Section: Discussionmentioning
confidence: 99%
“…; Martín‐Alcón et al. ). Q. coccifera L. and Q. ilex L. are common evergreen sclerophyllous oaks in Mediterranean areas of the Iberian Peninsula, whereas Q. faginea Lam.…”
Section: Methodsmentioning
confidence: 98%
“…; Martín‐Alcón et al. ). An increase in tree species diversity is generally thought to enhance the forest resilience to environmental changes, including variations in disturbance regimes (e.g.…”
Section: Introductionmentioning
confidence: 98%